Future Bearing Surfaces in Total Hip Arthroplasty - Chang, Jun-Dong (The Korean Orthopaedic Association, 2014)
One of the most important issues in the modern total hip arthroplasty (THA) is the bearing surface. Extensive research on bearing surfaces is being conducted to seek an ideal bearing surface for THA. The ideal bearing surface for THA should have superior wear characteristics and should be durable, bio-inert, cost-effective, and easy to implant. However, bearing surfaces that are currently being implemented do not completely fulfill these requirements, especially for young individuals for whom implant longevity is paramount. Even though various new bearing surfaces have been investigated, research is still ongoing, and only short-term results have been reported from clinical trials. Future bearing surfaces can be developed in the following ways: (1) change in design, (2) further improvement of polyethylene, (3) surface modification of the metal, (4) improvement in the ceramic, and (5) use of alternative, new materials. One way to reduce wear and impingement in THA is to make changes in its design by using a large femoral head, a monobloc metal shell with preassembled ceramic liner, dual mobility cups, a combination of different bearing surfaces, etc. Polyethylene has improved over time with the development of highly crosslinked polyethylene. Further improvements can be made by reinforcing it with vitamin E or multiwalled carbon nanotubes and by performing a surface modification with a biomembrane. Surface modifications with titanium nitride or titanium niobium nitride are implemented to try to improve the metal bearings. The advance to the fourth generation ceramics has shown relatively promising results, even in young patients. Nevertheless, further improvement is required to reduce fragility and squeaking. Alternative materials like diamond coatings on surfaces, carbon based composite materials, oxidized zirconium, silicon nitride, and sapphire are being sought. However, long-term studies are necessary to confirm the efficacy of these surfaces after enhancements have been made with regard to fixation technique and implant quality.